Introduction - Anabela Rato; Suzi Lima (Diacrítica, 2019)
This thematic volume Experimental Linguistics and Portuguese Language Varieties is dedicated to research that explores the interaction between linguistic theories and experimental methods in the areas of phonetics and phonology, morphology, syntax, semantics, sociolinguistics and second language acquisition.